An Empirical study of Market Strength of Firms and Its Influence on Accounting and non-Accounting Measures Using the Balanced Scorecard Concept - Krishnan, Anbalagan; Ravindran, R. (Intellectbase International Consortium, 2013)
The firm's market position strength is referred to as the extent of share in the market, in a particular business segment. The firm's market strength has a significant influence on the performance measures of the Performance Measurement System (PMS). As highlighted in the literature a firm operating in a strong market position, requires greater internal communication as compared to a firm which operates in a weak market position. Hence, to a greater extent emphasis on non-financial performance measures in addition to financial measures are dependent on market strength. The literature discussion has concluded that the firm which has a strong market position places greater demand on the subjective performance measures of PMS, than the firm with a weak market position. Analysis of Independent sample t-test results have provided sufficient evidence to show that the influence of two different market positions on performance measures differs and this has been confirmed with the mean analysis. Analysis of results revealed that firms that hold a strong market position concentrate on growth through product and human capital development while firms with weak market position focus on maintaining current stream of cash inflow. On whole this paper provides a detailed discussion of the firm's market strength and its influence on performance measures.